THE ARABIDOPSIS NHX1 GENE: OVEREXPRESSION AND ITS IMPACT ON SALT TOLERANCE IN TRANSGENIC PLANTS - KHAN , OU; AHMAD , B; MAMOONA , Z; IRFAN , Z; ISMAIL , A; SALEEM , S; SHAHEEN , M; KHAN , MAS; ZAFAR , M; BASHIR , MW (Biological and Clinical Sciences Research Journal, 2024)
Abiotic stresses, such as salinity, negatively impact crop growth, development and overall production. The discovery and operational confirmation of new genes will provide the framework for successful genetic engineering techniques to increase crop plants’ resistance to salinity stress. The most effective method for maintaining ionic balance in plants under stress due to saltiness is provided by the membrane and vacuolar Na+/H+ counter transporter. The function of AtNHX1, the initially identified vacuolar antiporter from more advanced crops, was extensively researched. In this article, we will review the possible function of the Arabidopsis NHX1 gene that is responsible for salt tolerance and its transformation into Wheat, Barley, Poplar, Fescue, Petunia hybrid, Alfalfa & Soybean. Reason to engineer higher plants’ genomes using Arabidopsis NHX1 genes to provide food sustainably in salinity-affected locations.